2020
DOI: 10.1249/mss.0000000000002139
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Timing on Glycemic Control: A Randomized Clinical Trial

Abstract: Despite the acknowledgment of exercise as a cornerstone in the management of type 2 diabetes (T2D), the importance of exercise timing has only recently been considered. Purpose This study sought to determine the effect of diurnal exercise timing on glycemic control in individuals enrolled in a 12-wk supervised multimodal exercise training program. A secondary aim was to determine the effect of diurnal exercise timing on the circadian rhythm of wrist skin temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 35 publications
1
64
0
Order By: Relevance
“…Mancilla et al [ 9 ] found that compared with participants who trained in the morning (a combination of aerobic and resistance-based exercises), participants who undertook the same training in the afternoon had better peripheral insulin sensitivity, insulin-mediated suppression of adipose tissue lipolysis, and fasting plasma glucose levels. However, glycaemic control and postprandial responses were similarly improved after 12 weeks of combined endurance and resistance exercise training undertaken in the morning vs evening in men and women with and without type 2 diabetes [ 10 ]. Long-term training studies incorporating early vs late training interventions are urgently needed to interrogate the effects of time of day specific exercise on metabolism and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mancilla et al [ 9 ] found that compared with participants who trained in the morning (a combination of aerobic and resistance-based exercises), participants who undertook the same training in the afternoon had better peripheral insulin sensitivity, insulin-mediated suppression of adipose tissue lipolysis, and fasting plasma glucose levels. However, glycaemic control and postprandial responses were similarly improved after 12 weeks of combined endurance and resistance exercise training undertaken in the morning vs evening in men and women with and without type 2 diabetes [ 10 ]. Long-term training studies incorporating early vs late training interventions are urgently needed to interrogate the effects of time of day specific exercise on metabolism and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Teo et al [ 10 ] reported similar benefits for a range of glycaemic measures after 12 weeks of either morning or evening exercise in individuals with and without type 2 diabetes. However, in these studies [ 8 10 ] neither the timing nor composition of meals was controlled, making it difficult to determine whether exercise timing or other factors underpinned the improvements in glucose profiles. Here we measured whole-body and blood biomarkers and used high-throughput serum metabolomics to determine the interactive effects of the consumption of a standardised high-fat diet (HFD) and daily exercise training undertaken either in the morning or evening on markers of cardiometabolic health and profiles of circulating metabolites in overweight/obese men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all studies agree that afternoon is the best time to exercise. Teo et al [ 118 ] demonstrated that 12 w of aerobic plus resistance exercise improved glycemic control whether performed in the morning or afternoon in adults with T2DM. Additionally, varied responses by sex to exercise timing when adjustments for activity level were considered in adults with T2DM suggests men who performed midday MVPA presented with lower cardiorespiratory fitness, whereas those who performed more morning activity presented with the highest cardiorespiratory fitness [ 3 ].…”
Section: Exercise Timing With Proximal Nutritionmentioning
confidence: 99%
“…In other clinical populations, for example individuals with obesity, habitually engaging in moderate to high-intensity continuous aerobic exercise in the morning hours (AM) has been shown to be more effective in promoting weight loss, and reductions in body fat and waist circumference compared with habitually exercising in the afternoon and evening hours (PM) [ 21 , 22 ]. Additionally, among individuals with type 2 diabetes but without cancer, habitually engaging in aerobic and resistance exercise in the morning hours has demonstrated superior utility in improving glycemic control [ 23 ] compared with habitual engagement in afternoon and evening exercise. On the other hand, afternoon and evening exercise is associated with greater exercise capacity, which may contribute to observations related to optimal changes in markers of human performance and physical function with habitual engagement in afternoon and evening exercise [ 24 ]; but mechanisms have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%